2017
DOI: 10.1080/20445911.2017.1321553
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linguistic phonotactic competition and cognitive control in bilinguals

Abstract: The current study examines the relation between cognitive control and linguistic competition resolution at the sublexical level in bilinguals. Twenty-one Spanish-English bilinguals and 23 English monolinguals completed a non-linguistic Stroop task (indexing inhibitory control) and a linguistic priming/lexical decision task (indexing Spanish phonotactic constraint competition during English comprehension). More efficient Stroop performance (i.e., a smaller Stroop effect) in bilinguals was associated with decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 48 publications
(98 reference statements)
1
20
0
Order By: Relevance
“…Such finding contradicts studies (15,16) which reported worse bilingual performance in speech perception in noise. On the other hand, studies conducted with the presence of conflicting information, in dichotic listening, found better performance of bilinguals when compared to monolinguals (6)(7)(8)(9)(10)(11)(12)13) .…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Such finding contradicts studies (15,16) which reported worse bilingual performance in speech perception in noise. On the other hand, studies conducted with the presence of conflicting information, in dichotic listening, found better performance of bilinguals when compared to monolinguals (6)(7)(8)(9)(10)(11)(12)13) .…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown positive effects on cognitive control, language (8,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) and the auditory system of individuals exposed to two different languages (6)(7)(8)(9)(10)(11)12) . Therefore, understanding speech recognition performance of bilinguals in different acoustic situations is extremely important to shed light on the influence of second language acquisition on the auditory system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations